Multicriteria and critical threshold value analyses in assessing sustainable forestry: model development and application - Mendoza, G.A.; Hartanto, H.; Prabhu, Ravi; Villanueva, T. (2002)
This paper presents different models designed to operationalize the principle of forest sustainability. Concepts such as resource or environmental utilization space, carrying capacity and critical thresholds are defined. The paper also describes an application of the qualitative and quantitative multicriteria models in assessing forest sustainability. Sustainability analysis was done in three stages: stage 1 involves the development of an appropriate set of criteria and indicators (C&I); stage 2 involves the use of multicriteria analysis (MCA) models for estimating relative importance of each C&I; and stage 3 involves the qualitative and quantitative assessment of each C&I. The qualitative model based on a simple flagging method where C&I elements are evaluated and assigned appropriate flag colors depending on the experts' judgements on their criticality. Similarly, the same set of C&I elements were also evaluated quantitatively using a scaled scoring system. These models were applied in a case study involving a community-managed forest in the Philippines. Feedback received from the assessors indicate that the models were found to be useful, transparent, and helpful tools in generating relevant sets of C&I and in evaluating these C&I with respect to overall forest sustainability.